Side effects and hypersensitivity reactions to corticosteroids - M.Z. Lisiecka (Medičnì Perspektivi)
The relevance of the topic under study is due to the fact that patients receiving large or repeated doses of corticosteroids often suffer from hypersensitivity reactions or side effects from taking this category of drugs. As a result, this poses a serious problem for healthcare authorities, as the scientific understanding of this phenomenon is still at an early stage. The purpose of study is to comprehensively disclose the various types of mechanisms underlying corticosteroid hypersensitivity, as well as to develop recommendations for more accurate methods of diagnosis, treatment, and prevention of this reaction. To achieve this goal, this theoretical study used various methods, including analysis, deduction, abstraction and generalization, and the method of synthesis. The results of the study underscore the broad spectrum of applications for corticosteroid drugs in medicine, highlighting their systemic effects and potential for side effects and hypersensitivity reactions across various bodily systems. These adverse reactions encompass hyperglycemia, hypertension, respiratory issues, visual impairments, skin conditions like contact dermatitis, bone tissue complications, and behavioral disorders, notably in children. Administering corticosteroids in COVID-19 treatment necessitates caution due to the potential for life-threatening immediate hypersensitivity reactions, which may be mistaken for disease progression. The results and conclusions of this study, which were formed using the above methods, may lead to a more accurate diagnosis of hypersensitivity to drugs such as corticosteroids, and may also contribute to the development of effective preventive measures. This study is of practical importance for dermatologists, allergists and immunologists, as well as researchers working in the field of rheumatology, allergology and immunology.